BUDAYA LITERASI MEDIA DALAM MENINGKATKAN DAYA BACA MAHASISWA IAIN CIREBON - Herawati, Lilik (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2017)
Media literacy is the ability of a person in using various media to access, analyze and produce information for various purposes in the daily life of students who will be influenced by the media around us in the form of television, film, radio, recorded music, newspapers and magazines, students do not know or ignore where the information comes from, which is important they can access it. Students’ literacy culture at IAIN Sheikh Nurjati Cirebon has a vertical relationship to the quality of students. The high interest in reading a book influences one's insight, mental, and behavior. There are many factors why IAIN Cirebon students’ literacy has a low percentage. This issue should get serious attention from the campus so that they 'read literacy' becomes a serious concern in all circles of society. When the state of literacy becomes a culture on IAIN campus it is not impossible to become a campus that not only succeeded in developing but also as an advanced campus.